2017
DOI: 10.1038/pcan.2017.6
|View full text |Cite
|
Sign up to set email alerts
|

Imaging response during therapy with radium-223 for castration-resistant prostate cancer with bone metastases—analysis of an international multicenter database

Abstract: Progression of bone metastases during radium-223 therapy is uncommon. A bone flare (pain and/or radiological) may be noted during the first 3 months, and should not be confused with progression. Imaging by CT scan should be considered after three and six doses of radium-223 to rule out extraskeletal disease progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 16 publications
2
42
0
2
Order By: Relevance
“…Prior retrospective series have demonstrated varying rates of bone and soft tissue progression with radium‐223. For example, a multicenter retrospective review of 130 men treated with radium‐223 reported CT progression in 46% (n = 57 of 124) and bone scan progression in only 6% (n = 6 of 99) of men with available imaging . Another retrospective series of 29 men treated with radium‐223 described improvement in bone scans in 14%, worsening of bone scans in 21%, and stable bone scans in 38% of men after radium‐223.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior retrospective series have demonstrated varying rates of bone and soft tissue progression with radium‐223. For example, a multicenter retrospective review of 130 men treated with radium‐223 reported CT progression in 46% (n = 57 of 124) and bone scan progression in only 6% (n = 6 of 99) of men with available imaging . Another retrospective series of 29 men treated with radium‐223 described improvement in bone scans in 14%, worsening of bone scans in 21%, and stable bone scans in 38% of men after radium‐223.…”
Section: Discussionmentioning
confidence: 99%
“…Radium‐223 was FDA approved on the basis of the Phase 3 ALSYMPCA trial, which demonstrated that radium‐223 improved overall survival and delayed the time to first symptomatic skeletal event, compared with placebo, among patients with symptomatic nonvisceral bone predominant metastatic castrate‐resistant prostate cancer (mCRPC) who had received, were not eligible to receive, or declined docetaxel. Notably, imaging was not obtained in ALSYMPCA, and retrospective series suggest variable rates of both soft tissue and bone progression over time with radium‐223 . As a result, the radiographic response to radium‐223 is poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…A recent multicenter study retrospectively evaluated CT and bone scintigraphy response in 130 patients treated with radium-223. 61 The authors concluded that bone progression was rare (6%), although a flare (pain and/or radiologic) phenomenon may be noted at 3 months and should not be confused with progression. CT imaging after 3 and 6 doses of radium-223 was suggested to rule out visceral disease progression that may necessitate discontinuing radium-223 in favor of chemotherapy or a new hormonal agent.…”
Section: Daniel Heinrich Et Almentioning
confidence: 99%
“…Disease monitoring in bone is problematic, with flare phenomena on computed tomography (CT) and bone scans reported. 44,61 Whole body magnetic resonance imaging (MRI) and positron emission tomography imaging are considered to be the best options for assessing the extent of disease, whereas MRI appears to be most promising for measuring response, 62 although this has not been validated for radium-223. However, MRI is not in regular clinical use owing to restricted resources.…”
Section: Daniel Heinrich Et Almentioning
confidence: 99%
See 1 more Smart Citation